Women in the Law Courts of Classical Athens - Kapparēs, Kōnstantinos A. (Intersectionality in Classical Antiquity Ser, 2021)
Intro -- Abbreviations -- Introduction -- Women and the legal system of the Athenian democracy: Why is it important? -- The intersection of the law with the lives of women -- Sources -- The modern literature -- Part I Cases Involving Women Litigants -- 1. Lysias , To Antigenes, on the Abortion -- 2. Lysias, On the Daughter of Antiphon -- 3. Hypereides, Against Aristagora, Aprostasiou (Two Speeches) -- 4. Deinarchos, That the Daughters of Aristophon Are Not Heiresses -- or, Diamartyria that the Daughter of Aristophon Is Not an Heiress -- 5. Pericles, In Defence of Aspasia, for Impiety -- 6. [Demosthenes] 40, To Boiotos on his Mother's Dowry -- 7. Hypereides, Against Demetria, Apostasiou -- 8. Lysias 32, Against Diogeiton: A Mother's Compelling Speech -- 9. Deinarchos, Synegoria to Hegelochos, for the Epikleros, or Against Hegelochos, Synegoria on Behalf of the Epikleros -- 10. Deinarchos, Against Hedyle, Apostasiou -- 11. Lysias, To Lais -- 12. [Deinarchos], Dispute Between the Priestess of Demeter and the Hierophant -- 13. Lycurgus, On the Priestess -- 14. Deinarchos, For an Epikleros: For the Daughter of Iophon -- 15. Euboulides, Against the Sister of Lakedaimonios, for Impiety -- 16. Hypereides, In Defence of Mika -- 17. Apollodoros, Against Neaira -- 18. Lysias, For Nikomache -- 19. Menekles, Against Ninos the Priestess, for Impiety -- 20. Lysias, On the Daughter of Onomakles -- 21. Isaios 3, On the Estate of Pyrrhos -- 22. Lysias, Against Philonides for Rape -- 23. Hypereides, In Defence of Phryne -- 24. Lysias, On the Daughter of Phrynichos -- 25. Isaios, To Satyros, for the Epikleros -- 26. Antiphon 1, Against the Stepmother for Poisoning -- 27. Demosthenes, Against Theoris, for Impiety -- 28. Hypereides, To Timandra -- Part II Women and the Athenian Justice System.